An effective self-driven PFC-PEC hybrid system for hydrogen generation from organic substance. (10th August 2017) - Liu, Xiao-He; Du, Fan; Chen, Qing-Yun; Wang, Yun-Hai
Graphical abstract: Highlights: A PEC-PFC hybrid system for effective hydrogen generation is demonstrated at zero bias. The generated photocurrent density of hybrid PEC-PFC system is 5 times than the PEC cell. H2 evolution rate reached ∼0.55 μmol/h in the PEC-PFC hybrid system. Abstract: Here, we report the feasibility and effectiveness of hydrogen generation based on solar light and organic substance degradation, by coupling a photoelectrochemical cell (PEC) and photo fuel cell (PFC) in a hybrid system. The PEC cell was consisted of a TiO2 nanorod arrays photoanode and a Pt cathode. The PFC was composed of the same photoanode and an air cathode. Under light illumination, PFC cell decomposed the glucose and converted its chemical energy into electric energy, simultaneously. In this hybrid PEC-PFC platform, the electricity produced by PFC serves as potential bias to the PEC cell with the aim to improve the photocurrent generated and hydrogen evolved. The hybrid PEC-PFC system generated a photocurrent density of 0.3 A m −2 (∼5 × enhancement) as compared with the stand-alone PEC cell (0.06 A m −2 ) under illumination (100 mW/cm 2 ). This increase in photocurrent density led to significantly improving in H2 production. Trace amount of H2 was observed in the PEC cell whereas H2 evolution rate was ∼0.55 μmol/h in the hybrid system. The successful demonstration of such a self-biased PEC-PFC hybrid system for hydrogen generation provides a new way for simultaneous clean energy recover and wastewater treatment.